Clinical and Biochemical Assessment of Hypogonadism in Type 2 Diabetic Men - Talukder, SK; Afsana, F; Latif, ZA; Pathan, F; Ashrafuzzaman, SM; Khan, SJ; Habib, SH; Saha, S (BIRDEM Medical Journal, 2012)
doi Aim: The aim of the study was to assess the prevalence of clinical hypogonadism in type 2 diabetic men based on clinical features and available biochemical measures. Materials and Methods: In this study carried out in a tertiary level hospital, serum concentration of total testosterone was measured in 170 type 2 diabetic (mean age 44.9±7.9 years) subjects who have erectile dysfunction or other features of hypogonadism. Results: The mean total testosterone concentration in type 2 diabetic men was 14.4±5.6 nmol/l. Fifty nine of 170 (34.7%) type 2 diabetic subjects had low serum testosterone levels (d12 nmol/L). Luteinizing hormone (LH) and follicle stimulating hormone (FSH) concentrations in type 2 diabetic men were inappropriately low with a very high prevalence of hypogonadotropic hypogonadism. BMI and waist circumference were both negatively correlated with testosterone levels, with the association being stronger for waist circumference. HbA1C level also reveal a negative association with sexual dysfunction and hypogonadotropic hypogonadism among type 2 diabetic men. Metabolic syndrome is also associated with the low serum testosterone levels in the study subjects. Conclusions: This study reveals that serum total testosterone levels are lower in diabetic men with signs/symptoms of hypogonadism. Hypogonadotropic hypogonadism is frequent in diabetic hypogondal population. There is an association between poor glycaemic control and hypogonadism in male diabetic persons. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12378 Birdem Med J 2011; 1(1): 3-9